2020
DOI: 10.29333/iji.2020.13152a
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Combining Communicative Traits of Writing with Cooperative Learning on Trainee Teachers’ Pedagogical Knowledge and Attitudes

Abstract: This article reports an investigation into the impact of presenting communicative traits of writing through cooperative learning on trainee teachers' pedagogical knowledge and attitudes towards a 'traits of writing' approach and cooperative learning. Mixed methodologies were used with the participants in a quasiexperimental repeated measure. Forty-two trainee teachers, enrolled in the Bahrain Teachers College, answered the pre and post pedagogical knowledge test and completed the two attitude scales at the end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Despite this, improvements in academic performance are often referred to as one of the greatest advantages or benefits of implementing cooperative learning [18,19]. As a result, there are multiple scientific reviews aimed at pre-service teachers in relation to their improved academic performance [11,[38][39][40]. It is certain that data extracted from our study showed the opposite line: A decrease in perceptions, thus affecting this variable negatively.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Despite this, improvements in academic performance are often referred to as one of the greatest advantages or benefits of implementing cooperative learning [18,19]. As a result, there are multiple scientific reviews aimed at pre-service teachers in relation to their improved academic performance [11,[38][39][40]. It is certain that data extracted from our study showed the opposite line: A decrease in perceptions, thus affecting this variable negatively.…”
Section: Discussionmentioning
confidence: 85%
“…Cooperative learning has been identified as one of the most promising methodologies, considering all types of teaching methods associated with fostering student growth. Consequently, in the last few years, extensive scientific reviews have been focused on pre-service teachers in relation to their improved academic performance [11,[38][39][40]; their motivation [41,42]; and their perceptions in group work [43][44][45].…”
Section: Related Workmentioning
confidence: 99%
“…Previous studies have documented the advantages of CL [3,24,[36][37][38], but few studies have specifically studied the advantages and challenges of CL from the university instructors' perceptions. However, given the benefits widely attributed to CL when it is implemented in school settings [39][40][41], investigating its potential benefits in university settings seems warranted. Furthermore, while almost all research supports the benefits of CL in western education, little research appears to have been conducted in other countries with different social, religious, education, and cultural systems [42].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have documented the advantages of CL [35,36,23,3,37], but few studies have specifically studied the advantages and challenges of CL from the university instructors' perceptions. However, given the benefits widely attributed to CL when it is implemented in school settings [38,39,40], investigating its potential benefits in university settings seems warranted. Furthermore, while almost all research supports the benefits of CL in western education, little research appears to have been conducted in other countries with different social, religious, education, and cultural systems [41].…”
Section: Introductionmentioning
confidence: 99%